Optimization of the number of channels of a multichannel radiometric receiver - Bykov, V. N.; Miroshnik, G. Yu.; Miroshnik, T. V. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2021)
Background: Improving the positioning accuracy of passive radiometric correlation-extreme navigation systems (RM CENS) of aircraft (AC) by landmarks depends on the ability of information RM sensors of systems to form two-dimensional images of ground objects in real time. The use of matrix RM sensors, which are based on multichannel RM receivers of the millimeter wave range (MMW), makes it possible to realize the required speed of the CENS Objectives: The aim of the work is to optimize the number of multiplexed channels per one amplifying-converting path of a multi-channel RM receiver with linear multiplexing and separation of channels according to the form of signals. Materials and methods: As an optimization criterion in this work, it is proposed to use the gain in sensitivity obtained as a result of the use of a multichannel RM receiver with linear multiplexing and signal waveform separation in comparison with the sensitivity of a RM receiver with time division multiplexing. Results: As a result of the analysis of the process of functioning of a multichannel RM receiver with time division multiplexing in this work a relation was obtained for the sensitivity of an individual channel of a RM receiver with time division multiplexing. Conclusions: It can be concluded that it is optimal to create a matrix RM receiver based on combining 16 RM channels of the superheterodyne type into one amplifier-conversion path. In this case, the total number of amplifying-converting paths is equal to four. The sensitivity of each channel remains high enough.